Long-term outcome of prosthesis-patient mismatch after transcatheter aortic valve replacement. (1st November 2020) - Compagnone, Miriam; Marchetti, Giulia; Taglieri, Nevio; Ghetti, Gabriele; Bruno, Antonio Giulio; Orzalkiewicz, Mateusz; Marrozzini, Cinzia; Bacchi Reggiani, Maria-Letizia; Palmerini, Tullio; Galiè, Nazzareno; Saia, Francesco
Abstract: Background: Incidence and long-term clinical consequences of prosthesis-patient mismatch (PPM) after transcatheter aortic valve replacement (TAVR) are still unclear. Methods: We enrolled 710 consecutive patients who underwent TAVR. PPM was defined as absent if the index orifice area (iEOA) was >0.85 cm2/m2, moderate if the iEOA was between 0.65 and 0.85 cm2/m2 or severe if the iEOA was <0.65 cm2/m2. Results: Among the 566 patients fulfilling the study criteria, the distribution of PPM was as follows: 50.5% none ( n = 286), 43% moderate PPM ( n = 243) and 6.5% severe PPM ( n = 37). At 5-year follow-up, patients with severe PPM had a significantly higher incidence of the combined endpoint of cardiovascular death, acute myocardial infarction and stroke ( p = .025) compared with the other patients. After adjusting the results for possible confounders, severe PPM remained an independent predictor of long-term adverse outcome (HR: 2.46; 95% Confidence Interval: 1.10–5.53). The independent predictors of severe PPM were valve-in-valve procedure and body mass index. Balloon-expandable valves were not associated with higher rates of severe PPM in comparison with self-expandable valves (8% vs. 5%, respectively, p = .245). Conclusions: In our study severe PPM emerged as a risk factor for long-term major adverse cardiac and cerebrovascular events. Highlights: Prosthesis-patient mismatch (PPM) after TAVR is common, although in most of the cases it is of moderate entity. The presence of severe PPM, but not of moderate PPM, is associated with a worse prognosis at 5 years. The independent predictors of severe PPM in our case series were valve-in-valve TAVR and body mass index.